Diversity, Distribution and Indigenous Uses of Medicinal Plants in Parbati Valley of Kullu District in Himachal Pradesh, Northwestern Himalaya - S.S. Samant2, Pankaj Sharma1* and (Journal of Medical Biomedical and Applied Sciences, 2014)
In the remote areas of the Indian Himalayan Region, the inhabitants largely depend on medicinal plants for curing diseases and income generation. But, proper documentation of the medicinal plants has been poorly attempted. The value of medicinal plants in traditional healthcare practices provides clues to latest areas of research in biodiversity conservation. Keeping this in view, the present study has been conducted to study the diversity, distribution and indigenous uses of medicinal plants of Parbati valley in Kullu district of the Himachal Pradesh. A total of 402 species of medicinal plants belonging to 98 families and 266 genera were recorded and used by the inhabitants of the area for curing various ailments. These medicinal plants comprise of 34 trees, 301 herbs, 61 shrubs, and climbers and ferns, 03 species, each. Maximum medicinal plants were reported in the altitudinal zone, 1100-1800m and decreased with increasing altitudes in the study area. Of the total medicinal plants, 207 were natives, 04 endemic and 44 near endemic. The continued over-exploitation, habitat degradation and changing environmental conditions may lead to the extinction of these species within a few years. Therefore, regular monitoring of population and habitats using standard ecological methods, development of conventional and in-vitropropagation protocols, establishment of species in in-situ and ex-situ conditions have been suggested.